THE RELATIONSHIP BETWEEN CONSUMER ETHNOCENTRISM AND PRODUCT NEEDS ON PURCHASE INTENTION IN PERSPECTIVE OF INDONESIAN CONSUMERS FOR CHINESE PRODUCTS ON TOKOPEDIA - Cindy Boennawan; Dewi Wuisan (Universitas Pelita Harapan, 2021)
The aim for this study is to understand the relationship between consumer attitude towards foreign product on e-commerce which analyzed through consumers ethnocentrism and product needs on purchase intention for Chinese products on Tokopedia. With globalization and technological advances, it is undeniable that e-commerce has become part of living to fulfill daily basis needs. Tokopedia, an Indonesian e-commerce under William Tanuwijaya as CEO has become one of the influences in Indonesian economy. However, even though Indonesia was mentioned to be Tokopedia’s largest contributor, Tokopedia falls behind Shopee, a Singapore e-commerce, that ranked number one in terms of monthly web visits and GMV (Gross Merchandise Value). The actual research was conducted on 178 respondents by using online questionnaires and the sampling technique was nonprobability purposive sampling. The subjects of this research are the people who have shopped in Tokopedia using the mobile app, and have the intention to shop again in the future. The data are processed through validity, reliability, and statistical analysis and performed using SmartPLS software. The results of the study indicate that Consumer Ethnocentrism have positive influences towards Attitude towards Foreign Products, this statement against previous research which states that the relationship between these hypotheses is negative.